16.9k views
2 votes
If f(x) = 2x2 + 3x and g(x) = x – 2, what is (f + g)(2)?

User Latiffany
by
5.3k points

2 Answers

5 votes

Answer:

14

Explanation:

First find an algebraic formula for (f + g)(x). To do this, combine like terms from f and g: (f + g)(x) = 2x^2 + 4x -2

Next, substitute 2 for x: (f + g)(2) = 2(2)^2 + 4(2) - 2 = 8 + 8 - 2 = 14

User StuperUser
by
5.0k points
4 votes

Answer:

14

Explanation:

(f + g)(x) = f(x) + g(x) = 2x² + 3x + x - 2 = 2x² + 4x - 2

To evaluate (f + g)(2) substitute x = 2 into (f + g)(x)

(f + g)(2) = 2(2)² + 4(2) - 2 = 8 + 8 - 2 = 14

User Gintas K
by
5.7k points